NILAI MORAL DALAM CERPEN “ANTING” KARYA RATNA INDRASWARI IBRAHIM - Aulia Zahra Fadhila; Ekarini Saraswati (Program Studi Pendidikan Bahasa Indonesia, STKIP Bina Bangsa Getsempena, 2022)
Short story is a literary work that has a story written by the author with one of the goals to provide a moral value for the reader. The short story